Comprehension Level Of Non-Technical Terms In Science: Are We Ready For Science In English - Ali, Maznah; Ismail, Zurida (Penerbit Universiti Sains Malaysia, 2006)
Most students find the learning of science not an easy task. These difficulties arise not only from the use of symbols to represent concepts, but also the language that must be mastered, in particular the technical and non-technical vocabulary. Students who learn science not in their first language face the problem of understanding both the scientific terminologies (technical terms) and regular explanation of the knowledge itself. Non-technical vocabulary refers to terms that have one or many meanings in everyday language but which have a precise and sometimes different meaning in a scientific context. Studies indicated that technical language of science posed a problem of familiarity, but students were seen to be able to cope reasonably well with this. Where a more acute problem lay, was in the use in science of normal, familiar language in a highly specific, often-changed and unfamiliar way. This paper will present the finding from a survey that aim at investigating form 4 students' comprehension of common nontechnical terms used in science. Sample consisted of 91 students (form 4 students of different streams – arts, science and engineering) who were requested to respond to 50-item questionnaire. Facilities index were calculated for each item. Analysis of the result showed that these students do encounter some difficulties in understanding the meanings of the non-technical terms.